(untitled) (Brazilian Journal of Radiation Sciences, 2019)
Currently, there is a need to produce new therapeutic techniques for the treatment of prostate tumors, considering the high incidence of the disease and significant morbidity rates associated with surgery and radiotherapy. Simulations in brachytherapy produce essential information about the efficiency and dosimetric efficacy compared to other techniques. This study estimated the efficiency of dosimetry by parameters of merit generated from volumetric distributions of absorbed doses simulating two spatial distributions of Ho-166 seeds in a prostate model. A computer voxel model was developed, using the SISCODES (Computational System for Dosimetry by Neutrons and Photons by Stochastic Methods applied to radiology and radiotherapy) code. The virtual model reproduced a cubic box, filled with muscle equivalent tissue (TE), in which a 5-cm diameter sphere with TE-prostate was positioned 2-cm from the air-interface. Two Ho-166 seed distributions were employed with distinct pitches: 9 and 10 mm, with same distance between seed of 8mm in a fillet (needle). The MCNP5 code generated the energy deposited per unit mass in each voxel .The spatial dose distributions were obtained for each of the seed distributions. The following parameters-of-merit were evaluated: maximum dose values and histograms. The parameters were compared between the two simulated groups. It was possible to evaluate the most appropriate distribution to the prostate brachytherapy, which has been shown to be a function of the injected seed activity.